Elective Pelvic Nodal Irradiation With a Simultaneous Hypofractionated Integrated Prostate Boost for Localised Prostate Cancer: Ready for Prime Time?. Issue 3 (March 2020) - Cheung, P.; Niazi, T.; Faria, S.; Loblaw, A.
Abstract: External beam radiotherapy is a standard treatment option for localised prostate cancer and hypofractionation has become an alternative to conventionally fractionated radiotherapy. In patients who receive external beam radiotherapy, elective pelvic nodal irradiation is sometimes delivered, especially in patients with unfavourable disease who are at risk of micrometastatic spread of cancer into the regional nodes. One elegant approach to combine prostate hypofractionation with elective pelvic nodal irradiation is with a simultaneous integrated boost technique, where a radical hypofractionated dose is delivered to the prostate while the regional pelvic nodes receive a lower microscopic dose simultaneously in a single radiotherapy plan over the same number of treatment fractions. This article reviews the existing published literature evaluating such an approach.